Gender Differences in Emotional Risk for Self- and Other-Directed Violence among Externalizing Adults - Sadeh, Naomi (2011)
OBJECTIVE: Women and men generally differ in how frequently they engage in other-and self-directed physical violence and may show distinct emotional risk factors for engagement in these high-impact behaviors. To inform this area, we investigated gender differences in the relationship of emotional tendencies (i.e., anger, hostility, and anhedonic depression) that may represent risk for other-directed (i.e., physical fighting, attacking others unprovoked) and self-directed violence (i.e., self-injury, suicide attempts). METHOD: The ethnically-diverse sample consisted of 372 adults (252 men and 120 women ages 18–55) with a history of criminal convictions. Facets of emotional risk assessed with the Aggression Questionnaire (Buss & Warren, 2000) and Mood and Anxiety Symptom Questionnaire (Watson et al., 1995) were entered simultaneously as explanatory variables in regression analyses to investigate their unique contributions to other- and self-directed physical violence in men and women. RESULTS: Analyses revealed anhedonic depressive tendencies negatively predicted other-directed violence and positively predicted self-directed violence in both men and women, consistent with a model of depression in which aggression is turned inwards (Henriksson et al., 1993). Gender differences, however, emerged for the differential contributions of anger and hostility to other-and self-directed violence. Specifically, trait anger (i.e., difficulty controlling one’s temper) was associated with other-directed violence selectively in men, whereas trait hostility (i.e., suspiciousness and alienation) was associated with self- and other-directed violence among women. CONCLUSIONS: The divergent findings for trait anger and hostility underscore the need to examine gender-specific risk factors for physical violence to avoid excluding potentially useful clinical features of these mental health outcomes.